SWATH fishing platform with higher propulsor efficiency - Güner, M; Atlar, M; Söylemez, M (SOC NAVAL ARCH MARINE ENG, 2001)
This paper presents the potential advantages of adapting a SWATH concept for a fishing vessel role with a specific emphasis on energy saving due to the use of a suitable unconventional propulsor. A fixed guide vane (or propeller/stator) type of propulsor, with its modest amount of efficiency improvement, has been recognized as one of the least complicated and robust unconventional energy saving devices among others. Thus, the paper presents a design methodology for this type of device and illustrates its successful application to a SWATH fishing vessel. The design methodology involves a three-dimensional model to predict the wake velocities around the axisymmetric SWATH lower hulls and an advanced lifting line procedure, which includes the deformation of the propeller's slipstream for the theoretical modeling of the stator and the propeller. The design application is carried out for a middle distance, water SWATH fishing platform, and efficiency gain due to the use of the stator is presented over a conventional screw propulsion system. The sensitivity of the stator design, with respect to main design parameters, which are the number of stator blades and the distance of the stator from the propeller, are investigated in addition to the advantages of adapting the SWATH concept as a fishing platform.
Keywords: Engineering; Oceanography